The Cancer Risk Profile of Systemic Lupus Erythematosus Patients. Issue 1 (January 2022) - Hardenbergh, Dylan; Naik, Rakhi; Manno, Rebecca; Azar, Antoine; Monroy Trujillo, Jose Manuel; Adler, Brittany; Haque, Uzma; Timlin, Homa
Abstract : Abstract: Systemic lupus erythematosus (SLE) patients have a well-established increased risk for cancer. Research from the past 2 decades has identified the specific malignancies that afflict SLE patients at disproportionate rates. Systemic lupus erythematosus patients are at heightened risk for several hematologic malignancies as well as for certain solid tumors, including lung, thyroid, and hepatobiliary cancers. They are at decreased risk for several cancers as well, including prostate and melanoma. Improved understanding of the unique cancer risk profile of SLE patients has led some professional societies to recommend specialized cancer screening and prevention measures for these patients and has enabled clinicians to better serve the SLE patient population.